O palácio de Deus e o templo do rei: a iconografia religiosa mineira e sua relação com os poderes constituídos - Dias, Marcos Horácio Gomes (2012)
ABSTRACT: The objective of this research is regarding the context of the appearance of Minas Gerais s art in the 18th century, marked by the Portuguese colonization and e statement of the Christian Catholic values. The works of that period are defined by the rhetoric and they are conditioned by the economy of the gold and for a society based on canons aristocrats and slavocrats. The history of Minas Gerais is characterized, above all, by a specific religiosity inside the Portuguese colonial territory marked by the secular organization of the orders third, brotherhoods and fraternities. In that sense, an entire artistic apparatus was important to show, to distinguish and to order that society that had been rich quickly, at the same time, that great sections of that same society were poor, enslaved and without perspective of life. The general objective of the research was to promote an analysis of the religious iconography of those different fraternities by analyzing the speech of the power of the monarch instituted at that time through the symbols and allegories crystallized in the artistic works of those groups. The more significant secular associations in Minas Gerais, due to the amount and quality of their temples and chapels, are: Order Third of Nossa Senhora do Carmo, Order Third of São Francisco de Assis, Fraternity of Nossa Senhora do Rosário and Fraternity of Nossa Senhora das Mercês. Specifically, it was aimed at determing the hagiografic narrative located in a colonial context as a result of a narrow relationship between Roman Catholicism and the Portuguese absolutist State